Maintenance treatment with rucaparib for recurrent ovarian carcinoma in ARIEL3, a randomized phase 3 trial: The effects of best response to last platinum‐based regimen and disease at baseline on efficacy and safety. (21st September 2021) - Oaknin, Ana; Oza, Amit M.; Lorusso, Domenica; Aghajanian, Carol; Dean, Andrew; Colombo, Nicoletta; Weberpals, Johanne I.; Clamp, Andrew R.; Scambia, Giovanni; Leary, Alexandra; Holloway, Robert W.; Amenedo Gancedo, Margarita; et al.
Abstract: Background: The efficacy and safety of rucaparib maintenance treatment in ARIEL3 were evaluated in subgroups based on best response to most recent platinum‐based chemotherapy and baseline disease. Methods: Patients were randomized 2:1 to receive either oral rucaparib at a dosage of 600 mg twice daily or placebo. Investigator‐assessed PFS was assessed in prespecified, nested cohorts: BRCA ‐mutated, homologous recombination deficient (HRD; BRCA mutated or wild‐type BRCA /high loss of heterozygosity), and the intent‐to‐treat (ITT) population. Results: Median PFS for patients in the ITT population with a complete response to most recent platinum‐based chemotherapy was 11.1 months in the rucaparib arm (126 patients) versus 5.6 months in the placebo arm (64 patients) (HR, 0.33 [95% CI, 0.23–0.48]), and in patients with a partial response (249 vs. 125), it was 9.0 versus 5.3 months (HR, 0.38 [0.30–0.49]). In subgroups of the ITT population based on baseline disease, median PFS was 8.2 versus 5.3 months (HR, 0.40 [0.28–0.57]) in patients with measurable disease (141 rucaparib vs. 66 placebo), 10.4 versus 4.5 months (HR, 0.31 [0.20–0.48]) in those with nonmeasurable but evaluable disease (104 vs. 56), and 14.1 versus 7.3 months (HR, 0.35 [0.24–0.51]) in those with no residual disease (130 vs. 67). Across subgroups, significantly longer median PFS was observed with rucaparib versus placebo in the BRCA ‐mutated and HRD cohorts. Objective responses were reported in patients with measurable disease and in patients with nonmeasurable but evaluable baseline disease. Safety was consistent across subgroups. Conclusion: Rucaparib maintenance treatment provided clinically meaningful efficacy benefits across subgroups based on response to last platinum‐based chemotherapy or baseline disease. Abstract : The efficacy and safety of the PARP inhibitor rucaparib as maintenance treatment for recurrent ovarian cancer were similar regardless of whether patients had a complete or partial response to their last platinum‐based chemotherapy or according to whether they had measurable, nonmeasurable but evaluable, or no residual disease at baseline. Rucaparib also reduced the disease burden in patients who had measurable or nonmeasurable but evaluable disease at baseline.